2010
DOI: 10.1007/s00586-010-1281-5
|View full text |Cite
|
Sign up to set email alerts
|

Kyphoplasty for the treatment of incomplete osteoporotic burst fractures

Abstract: Kyphoplasty has become a standard procedure in the treatment of painful osteoporotic compression fractures. According to current guidelines, involvement of the posterior wall of the vertebral body is a relative contraindication. From February 2002 until January 2008, 97 patients with at least one AO classification A 3.1 fracture were treated by kyphoplasty. There was a structured follow-up for the medium-term evaluation of the patients' outcome. Ninety-seven patients (68 of whom were females and 29 of whom wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 24 publications
1
45
0
6
Order By: Relevance
“…Using a different unit for describing re-alignment but kyphotic angles, Maestretti et al reported Beck Index improvements of 0.14 in their traumatic BKP case series treated with calciumphosphate cement [17] and Krüger et al of about 0.07 in their series of osteoporotic incomplete burst fractures [18]. However, in the latter series the preoperative BI values were around 0.8, whilst those in the Maestretti series were 0.7 and hence better comparable with the extent of VB deformation in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Using a different unit for describing re-alignment but kyphotic angles, Maestretti et al reported Beck Index improvements of 0.14 in their traumatic BKP case series treated with calciumphosphate cement [17] and Krüger et al of about 0.07 in their series of osteoporotic incomplete burst fractures [18]. However, in the latter series the preoperative BI values were around 0.8, whilst those in the Maestretti series were 0.7 and hence better comparable with the extent of VB deformation in our series.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that balloon kyphoplasty can be used in burst fractures in the elderly population [22]. The problem with using a balloon in burst fractures is the potential risk of pushing a posterior wall fragment further into the spinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…Die Beteiligung der Hinterwand im Rahmen von Berstungsbrüchen (Typ A3 nach Magerl) stellt aufgrund des erhöhten Risikos eines Zementaustritts in den Spinalkanal eine zumindest relative Kontraindikation zur Kyphoplastie dar [23]. Bei ausgeprägter Berstung des Wirbelkörpers empfiehlt sich auch hier die dorsale Stabilisierung [16]. Eine weitere Indikation zur dorsalen Stabilisierung stellen veraltete osteoporotische Wirbelkörperfrakturen mit posttraumatischer Kyphose dar, die durch Lagerung oder perkutane Maßnahmen nicht ausreichend lordosiert werden können.…”
Section: Die Behandlung Osteoporotischer Wirbelkörperfrakturen Mit Auunclassified